An endoscopic-assisted contralateral paramedian supracerebellar infratentorial approach in the treatment of thalamic hemorrhage with hematoma extension into the brainstem: a case report - Sun, Eryi; Lu, Siyuan; Chen, Bo; Wu, Qi (Frontiers in Surgery, 2023)
Objective Thalamic hemorrhage (TH) with hematoma extension into the brainstem can lead to poor outcomes. In this study, we discuss the feasibility of the endoscopic-assisted contralateral paramedian supracerebellar infratentorial (SCIT) approach as a therapeutic method for treating such patients. Case presentation A patient suffered from a sudden loss of consciousness and right limb weakness, and a CT scan indicated TH with hematoma extension into the brainstem. She consented to undergo surgery by the endoscopic-assisted contralateral paramedian SCIT approach. Results Now, the patient can open her eyes on her own and move her left arm in response to commands. Conclusion The endoscopic-assisted contralateral paramedian SCIT approach may be a viable therapeutic method for treating TH patients with hematoma extension into the brainstem.